Economic Feasibility Analysis of Sawaibu, Indonesia Bay Bridge Construction - Talaksoru, Alfred Sanny; Mudjanarko, Sri Wiwoho; Setiawan, Muhammad Ikhsan; Wahyuni, Atik (International Journal of Engineering, Science and Information Technology, 2023)
Sawaibu Bay Bridge is located in Manokwari Regency and is 300 meters long. The west side is on the Jalan Pahlawan canal, and the east is towards Jalan Siliwangi. This study assesses whether the bridge construction project is feasible and finds alternatives or solutions. The analytical methods used are NPV, BCR, and IRR, which refer to the value of inflation by considering the tourist retribution and travel time analysis. The results will be used to conclude whether the first alternative to the project meets the financial feasibility requirements based on inflation. It shows NPV of 67,061,982,402, BCR 1,096, and IRR 30% ? MARR of 10%, which means that the first alternative is feasible to build.